Étude préliminaire de la flore et de la biomasse ligneuse des clairières en haute altitude du Parc National de Kahuzi-Biega, République démocratique du Congo - Gérard Imani; Louis Zapfack; Prince Baraka; Isaac Ahana Mungu (VertigO)
Based on information from conservation services, we analyzed structural and dynamic features of clearings in Kahuzi-Biega National Park (between 2000 and 2300 asl). This analysis covered 15 years and aimed to characterize floristic structure, diversity, and estimate biomass/carbon of clearing. Trees with DBH more than 5 cm were counted and their height measured with laser within various plots. Various indexes and allometric equations were used in to characterize the vegetation and to estimate the biomass. One way Anova and TukeyHDS were also used in order to determine the trend of variation in the diversity and biomass distribution of the clearings. Species like Neoboutonia macrocalyx, Mimulopsis arborescens and Dombeya goetzenii are shown to be prominent in the the Kahuzi-Biega national Park between 2000 and 2300 asl.